2024
DOI: 10.1080/01652176.2023.2300943
|View full text |Cite
|
Sign up to set email alerts
|

Hypoxia-related Y RNA fragments as a novel potential biomarker for distinguishing metastatic oral melanoma from non-metastatic oral melanoma in dogs

MD Nazmul Hasan,
MD Mahfuzur Rahman,
Al Asmaul Husna
et al.

Abstract: Hypoxia may promote tumor progression, and hypoxically altered noncoding RNA (ncRNA) expression may play a role in metastasis. Canine oral melanoma (COM) frequently metastasizes, and ncRNA expression under hypoxia may be clinically significant. We aimed to elucidate ncRNA fragments whose expression is altered by hypoxia in COM-derived primary KMeC and metastatic LMeC cell lines using next-generation sequencing to validate these results in qRT-PCR, and then compare expression between metastatic and non-metastat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 28 publications
0
1
0
Order By: Relevance
“…Certain ncRNAs can serve as biomarkers for cancer as their expression correlates with specific cancer types or disease progression [ 151 ]. Evidence has demonstrated that ncRNAs play crucial roles for the early diagnosis, prognosis, and treatment of melanoma [ 152 , 153 ]. A recent meta-analysis found a combined sensitivity of long ncRNAs in diagnosing melanoma to be 72.4%, with a pooled specificity of 81.2% and an overall area under the curve (AUC) of 0.837.…”
Section: Risk Assessment Innovations and Personalized Medicine In Ski...mentioning
confidence: 99%
“…Certain ncRNAs can serve as biomarkers for cancer as their expression correlates with specific cancer types or disease progression [ 151 ]. Evidence has demonstrated that ncRNAs play crucial roles for the early diagnosis, prognosis, and treatment of melanoma [ 152 , 153 ]. A recent meta-analysis found a combined sensitivity of long ncRNAs in diagnosing melanoma to be 72.4%, with a pooled specificity of 81.2% and an overall area under the curve (AUC) of 0.837.…”
Section: Risk Assessment Innovations and Personalized Medicine In Ski...mentioning
confidence: 99%